Preparation of Highly Efficient Thermal Management Wearable Textiles: Electric Heating Properties and Structural Analysis of Conductive Textiles (Journal of Fiber Bioengineering and Informatics, 2024)
To prepare wearable personal thermal management fabric, conductive yarn was synthesised by in-situpolymerisation of polyaniline (PANI) and electroless silver plated nanoparticles (AgNPs) using acrylic(PAN) yarn as substrate. Subsequently, AgNPs/PANI/PAN conductive yarns of different structures arewoven. SEM, XRD and FT-IR characterised the structure and properties of AgNPs/PANI/PAN yarns.The resistance and temperature of fabric at different voltages were measured by four probe testers anda thermal infrared imager. The results show that when ${\rm AgNO}_3$ concentration is 10 g/L, the resistanceof AgNPs/PANI/PAN conductive yarn is 0.81 Ω/cm. At the same warp and weft density, the resistanceof the satin fabric is 0.272 Ω/sq, and the resistance of the plain fabric is 0.404 Ω/sq. When the voltageis 0.8 V, the equilibrium temperature of the satin fabric reaches $77.6 ^◦C,$ and that of the plain fabricreaches $63.4^◦C.$ With the increase of applied voltage, the heat loss of satin fabric decreases during theheating process.
Keywords: Acrylic Yarn; Polyaniline; Electroless Silver Plating; Electric Heating Performance.